2016
DOI: 10.14254/2071-789x.2016/9-1/12
|View full text |Cite
|
Sign up to set email alerts
|

Private Lessons as an Instrument for Middle Class Status Struggle in Post-socialist Societies: Poland and Ukraine Case Studies

Abstract: The aim of the article is to present the results of the research on taking private lessons among Polish and Ukrainian youth. The research was conducted in Polish-Ukrainian borderlands among upper secondary school graduates, with the use of survey method. 717 respondents were Polish, whereas 584 were Ukrainian. The results of research show that 62% of Polish students were taking private lessons, while in the Ukraine the number was 69%. Private lessons were taken especially by the students whose parents were edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
(8 reference statements)
1
3
0
2
Order By: Relevance
“…Hawrot (2018) showed that Polish students with learning difficulties from wealthier families used paid out-of-school learning assistance more often than their poorer peers. We also identified other studies for Poland with consistent results (Długosz, 2016;Kotarski, 2020).…”
Section: Determinants Of Children's Participation In Additional Classessupporting
confidence: 85%
“…Hawrot (2018) showed that Polish students with learning difficulties from wealthier families used paid out-of-school learning assistance more often than their poorer peers. We also identified other studies for Poland with consistent results (Długosz, 2016;Kotarski, 2020).…”
Section: Determinants Of Children's Participation In Additional Classessupporting
confidence: 85%
“…Overcoming indoctrination will certainly contribute to the democratisation and development of the middle class. According to the results of the research of the Polish researcher Petr Długosz (Długosz, 2016), it is the representatives of the middle class (those with higher education, better economic status, higher cultural capital) who strive to take extra paid lessons for their children (62% of Polish students and 69% of Ukrainian students) in order to participate in the struggle for high social positions.…”
Section: Middle Class and Democracy In Ukrainementioning
confidence: 99%
“…Polish middle-class parents have had special motivations to adapt to the consequences of the reform, providing private lessons and looking for less crowded, but high-ranking, schools for their children outside of the area where they live (e.g., close to the workplace of one of the parents). 50 according to research conducted in 2020 by the Public Opinion Research Center, 77 percent of Poles classified themselves as members of the middle class, of whom 14 percent saw themselves as lowermiddle class, 46 percent as "proper" middle class, and 17 percent as upper-middle class. as this research shows, the key factor of self-identification is the economic situation; this, in turn, correlates with the education level achieved.…”
Section: The Ways Policy Makers Reform the Systemmentioning
confidence: 99%